Aid For Trade as finance for the Poor - Jaime de Melo; Laurent Wagner (Fondation pour les études et recherches sur le développement international (FERDI), 2015)
The Aid for Trade (AFT) Initiative was announced at the 2005 Hong-Kong World Trade Organisation (WTO) ministerial. Then, Doha round talks were stalled as developing countries were disenchanted with the world trading system they had signed up to a decade earlier under the Single Undertaking, whereby all members signed up to the same rules even though differential treatment for the Least Developed Countries (LDCs) provided some preferential market access to OECD markets and longer time periods to implement the obligations. So when the AFT was started, market access to OECD countries had not improved because of dirty tariffication in agriculture, technical assistance funding to help implement the WTO agreements (customs valuation, sanitary and phytosanitary measures, trade-related aspects of intellectual property rights) was not forthcoming and for the LDCs preferential access was dwindling as preferential agreements signed by developed countries were proliferating.This paper focusses on channels through which AFT flows might help reduce poverty, the top priority– under the MDGs (goal 1A is "Halve, between 1990 and 2015, the proportion of people living on less than 1.25 a day"). It does not deal with the voluminous literature covering the aid-growth nexus. At around 30 billion a year, AFT is about 30% of Official Development Assistance (ODA) financial flows to developing countries (remittance flows are more than the combined ODA and FDI flows). So trying to isolate the effects of AFT from other financial flows is looking for a needle in a haystack. Hence the focus is about the channels linking AFT to poverty reduction through trickle down effects and a reduction in trade costs; as well as on multiple rather than single-country studies to emphasize generalizable results.[1]Section 1 reviews briefly the history of the AFT Initiative and the challenges it faces and section 2 discusses how the adding of objectives has complicated the evaluation of AFT. Section 3 contends that the evidence supports the view that trade is the engine of growth rather than the other way around and section 4 gives evidence of the trickle down effects of growth. Section 5 reports the evidence on the obstacles to trade caused by poor infrastructure and on the links between AFT disbursements and reduced trade costs. Section 6 concludes that the recently signed Trade Facilitation Agreement provides the opportunity to direct resources towards countries with the highest trade costs and highest poverty rates. [1] Cadot et al (2014) and Cadot and de Melo (2014a, b, c) provide a critical survey of what we know (and don't know) about the efficacy of aid-for-trade with a greater focus on lessons from case studies.
Keywords: F35; O19; 330